Improvement of Antitumor Efficacy by Combination of Thermosensitive Liposome with High-Intensity Focused Ultrasound - Cha, Jae Min; You, Dong Gil; Choi, Eun Jung; Park, Sang Jun; Um, Wooram; Jeon, Jueun; Kim, Kwangmeyung; Kwon, Ick Chan; Park, Jae Chan; Kim, Hyun Ryoung; Park, Jae Hyung (AMER SCIENTIFIC PUBLISHERS, 2016)
High intensity focused ultrasound (HIFU), allowing for precise heating of the deep and local area, is emerging as the source of mild hyperthermia for delivery of doxorubicin (DOX) using thermosensitive liposomes (TSLs). Conventionally, HIFU has been used for intravascular drug release at tumor tissue by inducing mild hyperthermia immediately upon systemic administration of DOX-TSLs. This immediate heating approach (IHA), however, limits the deep penetration of DOX for high anticancer efficacy. In an attempt to maximize the accumulation of DOX at tumor, the delayed heating approach (DHA) has been explored. In this approach, DOX-TSLs were intravenously administered into the tumor-bearing mice after pre-treatment of tumor tissue with HIFU to increase vascular permeability. We developed the fatty acid-cojugated elastin-like polypeptide bearing TSL (FTSL). The DOX-loaded FTSLs had a hydrodynamic size of 142 nm. In vivo biodistribution study demonstrated that DOX-FTSLs were selectively accumulated at tumor tissue with the maximum amount of DOX at 6 h post-injection. Thereafter, the tumor tissue was heated to 42 degrees C to induce rapid release of DOX from FTSLs. The results have demonstrated that, compared to IHA, DHA significantly enhances the antitumor efficacy of DOX-FTSLs because of their effective penetration to tumor tissue via the enhanced permeation retention effect, followed by rapid release of DOX.